Recognition of the Taliban: Challenges and Opportunities for Victims of Terrorism to Receive Compensation - Samuel Fishbein (Washington University Global Studies Law Review, 2025)
On August 30, 2021, the United States withdrew its last remaining troops from Afghanistan, marking the end of the longest armed conflict in American history. The withdrawal of American forces was preceded by a February 2020 agreement between the Trump administration and the Taliban which provided for the withdrawal of American forces from Afghanistan in the following fourteen months known as the Doha Agreement. Following his election in 2020, President Biden extended the deadline for withdrawal of American troops, stating that all U.S. forces would be withdrawn from Afghanistan by September 11, 2021. The Taliban subsequently seized wide swathes of Afghan territory in the summer of 2021,4 culminating with the capture of the capital of Afghanistan, Kabul, on August 15, 2021. Upon the fall of the existing Afghan government and the Taliban’s seizure of power, the Biden administration notified U.S. financial institutions that it did not recognize the Taliban as having control over Afghan national bank assets. The Taliban now has effective control over Afghanistan despite not being currently recognized by the United States as the official government of Afghanistan. In the aftermath of the Taliban assumption of power in Afghanistan, the Biden administration froze 7 billion of assets held by Afghanistan’s national bank, Da Afghanistan Bank (“DAB”), that were held in the United States.s The seized funds were later separated into two pools, one that would go to a third-party humanitarian trust to help the Afghan people and another that would remain in the United States, subject to attempts at attachment by plaintiffs with judgments against the Taliban. Victims of the September 11th terrorist attacks and other attacks assisted or perpetrated by the Taliban have already secured default judgments against the Taliban for amounts up to 6 billion. This note will examine the effects of the Taliban takeover of Afghanistan on the efforts of plaintiffs who have secured judgments against the Taliban to attach assets belonging to the DAB in satisfaction of awards against the Taliban. Specifically, this note examines the legal mechanisms that President Biden used to seize the DAB’s assets held in the United States following the Taliban takeover of Afghanistan. The note also examines the process and challenges plaintiffs face in suits against the Taliban in attempting to attach DAB assets. Part I of the note focuses on the background of American withdrawal from Afghanistan and the ensuing humanitarian crisis, current suits against the Taliban, Biden administration policy concerns regarding Afghanistan, and the Biden administration’s seizure and subsequent division of DAB assets held within the United States. Part II of the note analyzes both the avenues and challenges plaintiffs in suits against the Taliban face in attaching DAB assets to satisfy judgments against the Taliban. Part III of the note examines the current state of litigation that is attempting to attach DAB assets, and what, if anything, President Biden could do to effectuate his policy goals stated in part II while helping plaintiffs satisfy their judgments.
Keywords: Afghanistan; armed conflict; trump administration; taliban; victims of terrorism; compensation; humanitarian; terrorist attack; humanitarian crisis; assets; biden